2005
DOI: 10.1113/expphysiol.2004.029504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole body resistance training on arterial compliance in young men

Abstract: The effect of resistance training on arterial stiffening is controversial. We tested the hypothesis that resistance training would not alter central arterial compliance. Young healthy men (age, 23 ± 3.9 (mean ± S.E.M.) years; n = 28,) were whole-body resistance trained five times a week for 12 weeks, using a rotating 3-day split-body routine. Resting brachial blood pressure (BP), carotid pulse pressure, carotid cross-sectional compliance (CSC), carotid initima-media thickness (IMT) and left ventricular dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 20 publications
(54 reference statements)
10
101
1
4
Order By: Relevance
“…That is, it is thought that CRT is the contraction system 13,14 that brings about an increase of blood pressure, due to local compressive forces, which further elevates blood pressure, increasing arterial stiffness. At the same time, Rakobowchuk et al 9 reported that carotid IMT and cardiac dimensions were unchanged. In this study, carotid IMT, carotid lumen diameter and IMT/lumen were unchanged.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…That is, it is thought that CRT is the contraction system 13,14 that brings about an increase of blood pressure, due to local compressive forces, which further elevates blood pressure, increasing arterial stiffness. At the same time, Rakobowchuk et al 9 reported that carotid IMT and cardiac dimensions were unchanged. In this study, carotid IMT, carotid lumen diameter and IMT/lumen were unchanged.…”
Section: Discussionmentioning
confidence: 81%
“…Rakobowchuk et al 9 reported that carotid crosssectional compliance and carotid arterial stiffness was unchanged by 12 weeks of RT. This result differs from that of previous CRT results in this study and that of Miyachi et al 8 One cause for the difference between the results of this study and that of Rakobowchuk et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,41 Miyachi et al 11 reported a 19% decrease in central arterial compliance following 4 months of strength training in 14 young men compared to sedentary controls, but with no changes in peripheral compliance. It should be noted that not all studies have shown an increase in central arterial stiffness following resistance training, 42 but these studies included different populations and employed a different exercise prescription. We also observed small but significant increases in peripheral stiffness following 4 weeks of resistance training.…”
Section: Aementioning
confidence: 99%